(untitled) (European Journal of Pure and Applied Mathematics, 2011)
In our paper, we study a class Â WR (Î»,Î²,Î±,Î¼,Î¸), which consists of analytic and univalent functions with negative coefficients in the open unit disk U = z âˆˆ C : |z| < 1 defined by Hadamard product (or convolution) with Rafid - Operator, we obtain coefficient bounds and extreme points for this class. Also distortion theorem using fractional calculus techniques and some results for this class are obtained.